Relationships between self-construal, social comparison and job satisfaction with organizational commitment among young working adults in Malaysia - Wong, Swee Mun (2015)
Organizational commitment among young working adults has significant influence on the high employee turnover rate. Recent research found that Malaysian employees showed highest turnover rate among seven countries being surveyed. In addition,loyalty towards the organization also found decreased among young working adults.The purpose of this study aimed to examine the relationships between self-construal,social comparison, job satisfaction and organizational commitment among young working adults in Malaysia. The present study also determined the mediating effect of job satisfaction on the relationships between self-construal with organizational commitment and between social comparison with organizational commitment. A total of 420 young working adults in Malaysia aged between 21 to 30 years (M=26.30 years, SD=1.82) participated in the present study with 96.7% response rate. All data were collected using self-administered questionnaires via online survey. The revised version of Organizational Commitment Questionnaire (OCQ), Job Satisfaction Survey (JSS), Self-Construal Scale (SCS) and Social Comparison Scale were used to assess young working adults’ perception on each variable. SPSS software was used for analysis the data. Descriptive statistics, Pearson’s correlation and regression analysis were also used in this study. Results showed that there were more young working adults who claimed themselves as interdependent self (n=196) than independent self (n=188). In addition, findings from Pearson’s correlation analyses showed that self-construal (r = .29,p<.001), social comparison (r = .52, p<.001) and job satisfaction (r = .40, p<.001) were significantly positive correlated with organizational commitment. The findings also indicated that self-construal, social comparison and job satisfaction were significantly associated with all three organizational commitment constructs, namely affective commitment, continuance commitment and normative commitment. Hence, regression analyses were performed when all variables showed significant relationships. On the other hand, two series of regression equations were performed to assess the mediating effect of job satisfaction between self-construal and social comparison on organizational commitment. The findings showed that there was a significant partial mediation on the influence of self-construal on organizational commitment through job satisfaction. Also,there was a significant partial mediation on influence of social comparison on organizational commitment through job satisfaction. Therefore, job satisfaction considered as an important factor which may enhance organizational commitment level of young working adults in Malaysia. Theoretically, the present findings underlined the role of self-perceptions in influencing the attitudes on job and organizations that they worked with among young working adults as a whole. Practically, the findings implied that organizations should take into account young working adult’s perspectives on their current job in order to create committed workforce.